2g+5=-3

Simple and best practice solution for 2g+5=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g+5=-3 equation:


Simplifying
2g + 5 = -3

Reorder the terms:
5 + 2g = -3

Solving
5 + 2g = -3

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 2g = -3 + -5

Combine like terms: 5 + -5 = 0
0 + 2g = -3 + -5
2g = -3 + -5

Combine like terms: -3 + -5 = -8
2g = -8

Divide each side by '2'.
g = -4

Simplifying
g = -4

See similar equations:

| (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) |

Equations solver categories